The linguistic markers of the language variety spoken by gang members on the Cape Flats, according to the film Dollars and White Pipes - Paterson, Moya Colleen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2008.